Wideband horizontally polarized omni-directional antenna - Yufeng Yu; Qingfeng Dai; Linglu Chen (2016 Progress in Electromagnetic Research Symposium (PIERS), 2016)
The paper presents a wideband omni-directional horizontally polarized (HP) antenna utilizing four modified T-bar fed cavity-backed slot antenna (CBSA) elements. The wide bandwidth of the antenna is guaranteed by the wideband CBSA elements. The proposed antenna achieves a 76% (443 MHz ~ 992 MHz) bandwidth for VSWR ≤ 2. The antenna size is 260 mm × 260 mm × 420 mm, which is 0.38λ L × 0.38λ L × 0.62λ L (λ L is the wavelength at the lowest operating frequency 443 MHz). The average gain in the horizontal plane is from 0.2 dB to 3.2 dB from 450 MHz to 800 MHz while the gain variation is below 1.0 dB and increases dramatically above 800 MHz (2.6 dB at 850 MHz and 5.0 dB at 900 MHz). The proposed wideband omni-directional HP antenna may find applications in wireless communication systems, UHF band spectrum monitoring/jamming systems and TV signal reception devices.